2018
DOI: 10.18865/ed.28.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Racial Disparities in Stroke: The Wide Spectrum Investigation of Stroke Outcome Disparities on Multiple Levels (WISSDOM )

Abstract: <p class="Default">Racial-ethnic disparities in stroke recovery are well-established in the United States but the underlying causes are not well-understood. The typical assumption that racial-ethnic disparities in stroke recov­ery are explained by health care access inequities may be simplistic as access to stroke-related rehabilitation, for example, does not adequately explain the observed disparities. To approach the problem in a more comprehensive fashion, the Wide Spectrum Investigation of Stroke Out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…EJ is defined as “the fair treatment and meaningful involvement of all people regardless of race, color, national origin, or income, with respect to the development, implementation, and enforcement of environmental laws, regulations, and policies” (EPA, ). Nurses have played an important role in developing EJ body of knowledge and linking it to health disparities (Adams et al, ; Amiri & Zhao, , ; Flaskerud et al, ; Lee et al, ). EJ research aims to identify the relationship between the disproportionate burden of environmental risks associated with those underrepresented in decision‐making, racially diverse, marginalized, and disadvantaged populations.…”
Section: Discussionmentioning
confidence: 99%
“…EJ is defined as “the fair treatment and meaningful involvement of all people regardless of race, color, national origin, or income, with respect to the development, implementation, and enforcement of environmental laws, regulations, and policies” (EPA, ). Nurses have played an important role in developing EJ body of knowledge and linking it to health disparities (Adams et al, ; Amiri & Zhao, , ; Flaskerud et al, ; Lee et al, ). EJ research aims to identify the relationship between the disproportionate burden of environmental risks associated with those underrepresented in decision‐making, racially diverse, marginalized, and disadvantaged populations.…”
Section: Discussionmentioning
confidence: 99%
“…We recruited 60 community dwelling subjects, who were between the ages of 30–75 years of age, without a history of stroke, as part of the American Heart Association/American Stroke Association Strategically Funded Research Network funded Wide Spectrum Investigation of Stroke Outcome Disparities on Multiple Levels (WISSDOM) study [26]. All subjects self-reported that they were not currently pregnant (if female) and did not have a history of dementia, a diagnosis of substance abuse, or the presence of a terminal illness with life expectancy of ≤ 1 year.…”
Section: Methodsmentioning
confidence: 99%
“…[30][31][32] The Wide Spectrum Investigation of Stroke Outcome Disparities on Multiple Levels (WISSDOM) Center 30 grant, funded through the American Heart Association (AHA) Strategically Focused Research Network Disparities in Cardiovascular Disease and Stroke, explored stroke outcome disparities among persons with stroke residing in the Low country region of South Carolina and located within the stroke belt, a collection of states in the southeastern United States with the highest rates of stroke and other cardiometabolic diseases. 30,33,34 The CINGS (Community-Based Intervention Under Nurse Guidance After Stroke) study was a primary research emphasis within WISS-DOM and focused on family and community factors during the development and implementation of stroke interventions guided by nurses in conjunction with community health workers. The study, following local Institutional Review Board approval, used qualitative and quantitative methods during a multi-phased community-based participatory approach.…”
Section: Developing Community-based Interventions To Address Racial D...mentioning
confidence: 99%